Aligning Multiple Knowledge Perspectives in a Health Services System - Castleman, Tanya; Swatman, Paul Anthony; Fowler, Danielle (Idea Group, 2004)
This chapter reports the results of a feasibility study into electronic collection of service data at “point of delivery” for disability programs. The investigation revealed that while the proposed system would have produced more fine-grained data, it would not have improved any actor’s knowledge of service delivery. The study illustrated the importance of context in the transition from data to knowledge; the diffused and fragmented organisational structure of social service administration was shown to be a major barrier to effective building and sharing of knowledge. There was some value in the collection of detailed service data but this would have damaged the web of relationships which underpinned the system of service delivery and on which the smooth functioning of that system depended. The study recommended an approach to managing the informal and tacit knowledge distributed among many stakeholders, which was not especially technologically advanced but which supported, in a highly situated manner, the various stakeholders in this multi-organisational context.
Keywords: Health Information Systems; Medical & Healthcare IS&T; Medical Information Science Reference